Parents' Views on the Role of Male Teachers in Early Childhood Education - Yosifa Qolbi Noor; Asep Kurnia Jayadinata; Dhea Ardiyanti (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Ilmu Pendidikan, Universitas Negeri Makassar, 2025)
This study aims to examine parents' views on the usefulness and professional role of male teachers in the Early Childhood Education (ECE) unit. The background of this research stems from the low number of male teachers in ECE, both nationally and globally, which has led to various perceptions among parents, ranging from doubts about competence to recognition of the positive contributions of male teachers. The research method used is a phenomenological qualitative approach with interpretative phenomenological analysis, covering aspects of parental trust, professional competence, parenting roles, gender stereotypes, and acceptance and expectations. The respondents were ten parents of ECE students at TKIT Cendekia, Purwakarta. Participants were selected by purposive sampling, with the main criterion. The results of the study are expected to provide a comprehensive picture of the level of parental acceptance of male teachers, as well as identify factors that strengthen or weaken this trust. Theoretically, this research contributes to expanding the study of the role of gender in early childhood education. Practically, the results of the research can be the basis for ECE institutions and policymakers in designing strategies to increase the representation of male teachers and build effective communication with parents to reduce negative stereotypes.